Factors Affecting Cash Holding in Pharmaceutical Sub-Sector Manufacturing Companies - Sari, Agustin Rusiana; Maula, Fina Inayatul (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This study aimed to determine the effect of profitability, leverage, and firm size on cash holding in Pharmaceutical Sub-Sector Manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2017-2022. The sampling technique used in this study was purposive sampling, and seven company samples were obtained from 11 pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2017-2022. The analysis technique consists of descriptive statistical analysis and multiple linear regression analysis. The results showed that partial profitability positively affects cash holding, leverage hurts cash holding, and firm size has a positive effect on cash holding. Simultaneously, profitability, leverage, and firm size affect cash holding. The coefficient of determination is 0.537 or 53.7%, indicating that profitability, leverage, and firm size can explain cash holding by 53.7%. Other variables outside the research variables influence the remaining 46.3%.